(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2002)
Bed-by-bed lithostratigraphic sections combined with sequence stratigraphy and conodont biostratigraphy provide new information on the depositional environment and age of the Lipak Formation in the Pin Valley (Spiti). The formation comprises mixed siliciclastic and calcareous sediments at lower levels, richly fossiliferous limestones with two distinct sandstone incursions at higher levels, and dark mudstones followed by a thin siltstone interval. The upper limit of the Lipak Formation is defined by the angular unconformity below the sandstones of the Permian Gechang Formation. Lithologic correlation with sections in upper Lahaul indicates that, in the Pin Valley, the formation has been truncated just below its characteristic gypsum horizon. The lower boundary of the Lipak Formation is gradational from coastal arenites of the Muth Formation; the mappable boundary is drawn at the first appearance of dark carbonaceous, argillaceous siltstone and shale. Sedimentary structures, microfacies and conodont faunas indicate a general shallow marine depositional environment of the Lipak Formation in the Pin Valley; five sequence stratigraphic units have been distinguished. Conodont data demonstrate that the lowest 33 m of the Lipak Formation of the Pin Valley is mid to late Early varcus Subzone with characteristic species of Icriodus and Bipennatus. A previously unrecognised hiatus at c. 33 m above the base, at the boundary of sequence stratigraphic units S1 and S2, represents the interval Middle varcus Subzone to at least the end of the late Famennian Early expansa Zone. Because this hiatus does not correspond to a mappable boundary, no division of the Lipak Formation into named stratigraphic units is suggested, but we refer informally to the sediments represented by cycle S1 as Lipak A, and the sediments represented by cycles S2-S5 as Lipak B. Determination of S1 as Early varcus Subzone provides a maximum age for the gradationally underlying Muth Formation. At 75 m above the base of the composite Lipak Formation section, a 58 cm black to dark grey shale interval within late Famennian fossiliferous limestones conceivably correlates with the Hangenberg Event (end-Middle praesulcata Zone). Younger conodont faunas of the Lipak Formation -dominated by species of Clydagnathus with species of Bispathodus and Pseudopolygnathus also represented- is shown to extend to the mid-Tournaisian Early crenulata Zone.